Treatment of separate surgical cases in horses in the conditions of horse sports complex of Ireland - Peredera, R.; Aristova, O. (Scientific Progress & Innovations, 2025)
Nowadays, the role of horses in human life remains exceptionally important. These animals are used as draft force in the agrarian sector of many countries, the subdivisions of patrol police (mounted police squadrons), in treatment and rehabilitation programs (hippotherapy) as well as in numerous kinds of sports horse breeding. Therefore providing a high quality of horses’ life, maintaining their productivity and making the duration of their active use longer, in particular, sports life longevity, are among the priority tasks of veterinary medicine. With the growing popularity of equestrian sports and increasing the intensity of using horses in many horse sports complexes, a stable tendency is observed to the growth of the number of cases connected with surgical diseases as a result of traumatic injuries. This fact determines the urgent necessity to improve the modern approaches to prevention, early diagnostics and effective treatment of such pathological processes. Any pathological condition taking place in the horse body, inevitably leads to the decrease in the animals’ ability to work and endurance. Correspondingly, all the above mentioned has a negative impact on the sports career of horses. Therefore, the purpose of our studies was to highlight the data concerning the spread and describe separate clinical cases of horses’ surgical diseases that are registered in the horse sports complex of Ireland. The researches were conducted during 2024–2025 in one of the horse sports complexes of Ireland. General methods of study (examination, palpation, thermometry, percussion, auscultation, passive and active movements) and special methods with the use of specific veterinary equipment (X-ray apparatus, portable ultrasound unit, thermograph, endoscope, and others) were used in the work. It was found that surgical pathologies in horse sports complexes of Ireland are spread and characterized by a considerable frequency of occurrence; these pathologies pose organizational, economic, treatment and prevention difficulties both for the specialists of veterinary medicine and for owners of horses. For example, according to the data of veterinary documentation, collected by questioning of owners, coaches, and veterinary doctors about the anamnesis, the pathologies connected with the disorder of the support and movement system were most often registered. Based on the data of the documentation of Ireland’s horse sports complexes, the share of such disorders made 36.4 % of the total number of the registered surgical pathologies. Among them, 27.3 % required surgical intervention. This fact stresses upon the necessity of profound studying the reasons, mechanisms of the course and ways to optimize veterinary assistance.